A Content Analysis of the Journal of Intercollegiate Sport: 2008-2022 - Dylan Williams; Gregg Rich; Olivia Durham; Kevin Doran (Journal of Intercollegiate Sport)
Within the sport management discipline, college sport is a heavily researched area with many scholarly articles published in various academic journals. Such popularity has led to the creation of academic outlets focused exclusively on intercollegiate athletics such as the Journal of Intercollegiate Sport (JIS), which began in 2008. Because of the demand and creation of vehicles to disseminate college sport-focused research, it is vital to analyze the scholarly contributions found in these periodicals to identify what research has been conducted to identify potential strengths, weaknesses, and gaps. Such an analysis provides both scholars and educators with information regarding completed areas of research as well as potential gaps on a particular subject. Thus, the purpose of this project is to examine the content found in JIS from 2008 to 2022 to reveal its strengths, weaknesses, and areas where it can improve in the future.